Therapeutic Potential of Pterocarpus santalinus L.: An Update - Bulle, Saradamma; Reddyvari, Hymavathi; Nallanchakravarthula, Varadacharyulu; Vaddi, Damodara Reddy (Pharmacognosy Reviews)
Recently there has been increasing interest in plants and plant‑derived compounds as raw food and medicinal agents. In Ayurveda, an Indian system of traditional medicine, a wide spectrum of medicinal properties of Pterocarpus santalinus is described. Many important bioactive phytocompounds have been extracted and identified from the heartwood of P. santalinus. Bioactive compounds typically occur in small amounts and have more subtle effects than nutrients. These bioactive compounds influence cellular activities that modify the risk of disease rather than prevent deficiency diseases. A wide array of biological activities and potential health benefits of P. santalinus have been reported, including antioxidative, antidiabetic, antimicrobial, anticancer, and anti‑inflammatory properties, and protective effects on the liver, gastric mucosa, and nervous system. All these protective effects were attributed to bioactive compounds present in P. santalinus. The major bioactive compounds present in the heartwood of P. santalinus are santalin A and B, savinin, calocedrin, pterolinus K and L, and pterostilbenes. The bioactive compounds have potentially important health benefits: These compounds can act as antioxidants, enzyme inhibitors and inducers, inhibitors of receptor activities, and inducers and inhibitors of gene expression, among other actions. The present review aims to understand the pharmacological effects of P. santalinus on health and disease with “up-to-date” discussion.
Keywords: Antioxidant activity; oxidative stress; phytocompounds; Pterocarpus santalinus